La révolution au pluriel. Pour une historiographie de la question messaliste - Nedjib Sidi Moussa (L’Année du Maghreb)
This article provides an assessment of the revolutionary production of Messali Hadj and his partisans who were confronted with eclipse, stigmatization and rehabilitation. The text deals more particularly with the congress of Hornu to show the determinist character of the first narratives before turning toward a growing Messalist reappropriation which has accompanied the movement against authoritarianism in Algeria as well as the recent trend of literary popularization through the example of Mohammed Benchicou’s last novel.